RETRACTED: Regional Sustainable Development and Spatial Effects From the Perspective of Renewable Energy - Cai, Xiaowei; Wang, Wenjing; Rao, Amar; Rahim, Syed; Zhao, Xin (Frontiers in Environmental Science, 2022)
Green development is crucial for promoting high-quality and sustainable economic and social development. In China, green development is key to achieving the national goals of building a beautiful China and rejuvenating the nation. In this study, we employed a slacks-based measure data envelopment analysis method to calculate the green development efficiency value of panel data from Anhui Province, China, from 2005 to 2020. Moreover, the Malmquist Index was used to dynamically analyze the green total-factor productivity and decomposition index of 16 cities in Anhui Province. Exploratory spatial data analysis was used to measure the spatial relationship of the green development efficiency value for each province in Anhui Province. Then, STATA software was used to establish the spatial lag model according to the spatial correlation and perform a comprehensive analysis of the impact and spillover effects. The results show that: 1. The green development efficiency of various cities in Anhui province varies greatly, and gradually rises and maintains a relatively high value of green development efficiency after a fluctuation around 2012. 2. The green development efficiency values of various urban areas in Anhui province are clustered in space, and mainly in the “high, high and low” clustering situation 3. From the perspective of the regression results of spatial lag, economic development, industrial structure, the digital economy and the urbanization level is relatively significant positive correlation to the development of regional economic development, energy structure, the level of opening to the outside is significant negative correlation to regional green development efficiency, environmental governance, and no significant relationship between the level of science and technology development. 4. From the perspective of spillover effects of influencing factors, economic benefits, industrial structure and urbanization rate have positive and negative spillover effects on local regional green development, while the relative development of energy structure, digital economy and level of opening to the outside world have positive spillover effects on surrounding areas. It is of great significance to measure and study the green development level of regional economy.